2010
DOI: 10.1007/s00520-010-1056-x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with palliative care in patients with advanced cancer at a tertiary care hospital in a developing country

Abstract: The importance of palliative care in patients with advanced cancer is established. Reports on the experience with palliative care in the Middle East region are limited. A prospective study was performed to characterize the palliative care experience at a tertiary care center in Lebanon and to identify the profile of patients requiring palliative care. This communication highlights the results of the study. Authors conclude that the profile of needs for individuals requiring palliative care in Lebanon is simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Several studies have noted patients define fatigue as the most distressing of the symptoms they experience during their cancer intervention [27]. Our findings on fatigue are also supported by previous Arabic studies, which highlighted that fatigue seems to be the most frequent symptom among Arabic cancer patients with a prevalence rate of about 80% [12,13].…”
Section: Fatiguesupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have noted patients define fatigue as the most distressing of the symptoms they experience during their cancer intervention [27]. Our findings on fatigue are also supported by previous Arabic studies, which highlighted that fatigue seems to be the most frequent symptom among Arabic cancer patients with a prevalence rate of about 80% [12,13].…”
Section: Fatiguesupporting
confidence: 88%
“…Few studies in Saudi Arabia and other Arabic countries explore the psychological morbidity of cancer patients. Most studies were conducted in a palliative care clinic when cancer patients approached death [12][13][14].…”
Section: Problemsmentioning
confidence: 99%
“…(15) A study from Lebanon on cancer inpatients referred to PC showed that more than 95% had cancer pain and about 77% reported severe pain. (16) Internationally speaking, in a systematic review covering a period of four decades, the prevalence of pain in patients with advanced cancer was reported to be 64%. (17) More recently, a Canadian PC survey showed a prevalence of moderate to severe cancer pain approaching 34%.…”
Section: Discussionmentioning
confidence: 99%
“…[18] A recent report from Lebanon has shown high prevalence of fatigue (88.4%), dyspnea (65.1%), depression (53.5%), and confusion (37.2%) among inpatients with advanced cancer. [19] Alshemmari et al . from Kuwait have studied cancer patients who were largely having advanced incurable disease and found the most common nonpain symptoms to be fatigue (80%), anorexia (67%), weight loss (49%), and dyspnea (42%).…”
Section: Discussionmentioning
confidence: 99%